Endothelial cells augment the suppressive function of CD4+CD25+Foxp3+ regulatory T cells: involvement of programmed death-1 and IL-10 - Bedke, Tanja; Pretsch, Leah; Karakhanova, Svetlana; Enk, Alexander; Mahnke, Karsten (Molecular immunology, 2010)
Blood endothelial cells (ECs) act as gatekeepers to coordinate the extravasation of different T cell subpopulations. ECs express defined panels of adhesion molecules, facilitating interaction with blood circulating T cells. In addition to the mere adhesion, this cellular interaction between ECs and transmigrating T cells may also provide signals that affect the phenotype and function of the T cells. To test the effects of ECs on regulatory T cells (Treg) we set up cocultures of freshly isolated murine Treg and primary ECs and assessed the phenotype and function of the Treg. We show that Treg upregulate programmed death-1 (PD-1) receptor expression, as well IL-10 and TGF-β secretion after contact to ECs. These changes in phenotype were accompanied by an increased suppressive capacity of the Treg. Blockade of the PD-1 and/or the IL-10 secretion in the in vitro suppression assays abrogated the enhanced suppressive capacity, indicating relevance of these molecules for the enhanced suppressive activity of Treg. In aggregate, our data show, that ECs increase the immunosuppressive potential of activated Treg by upregulation of PD-1 and stimulation of the production of high levels of IL-10 and TGF-β. Therefore, one can speculate that Treg during transendothelial transmigration become “armed” for their suppressive function(s) to be carried out in peripheral tissues sites.